Emerging from the Global Crisis : Macroeconomic Challenges Facing Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
While the impact of the global crisis has been severe, real per capita GDP growth stayed positive in two-thirds of low-income countries (LICs), unlike in previous global downturns, and in contrast to richer countries. The crisis affected LICs not so much through the terms of trade or global interest rates, but rather through a sharp contraction in export demand, foreign direct investment, and remittances (oil exporters also suffered from a sharp fall in oil prices). LICs saw the sharpest decline in their economic growth rate over the last four decades. However, this slowdown followed a period of strong expansion, and real per capita GDP growth has generally held up in LICs, remaining well above growth in richer countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet